If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 6 = -24 Reorder the terms: 6 + x = -24 Solving 6 + x = -24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + x = -24 + -6 Combine like terms: 6 + -6 = 0 0 + x = -24 + -6 x = -24 + -6 Combine like terms: -24 + -6 = -30 x = -30 Simplifying x = -30
| 3(x+4)+2(x-1)=-5 | | 7(h+3)=6h-18 | | a-6=-24 | | 2w+2(2w-5)=80 | | 9x+30=15x | | -8-7x=-64 | | 12-9(8-7x)=6(8-x)-12x | | 6z=15-13 | | 6x+2-7x=6 | | 4(y+5)-6(2y+3)=3(y+14)-2(5-y)+9 | | -5=15-4y | | (a^2)(b^4)= | | 0.08x+0.06(300-x)=20 | | A-5=-1 | | 2w+2(2w-5)=26 | | 7x-1-4x=7 | | 6a+37=9-a | | 7y+8=-4+6y | | -6f=60-f | | 25-[10-(2-12)]+(5-343)= | | 6.4=.63x+4.51 | | -7+7x=-91 | | 14.35=-5.2 | | -3x+123=-12x-147 | | 55w+50(4.4-w)=233 | | 14x=8x | | K-6=4 | | 8x=14x | | -10=5(2x-4) | | x^2-6x-3=-6 | | 7n^2-6=106 | | f-(-.125)=.3 |